Invigorating employee’s innovative work behavior: exploring the sequential mediating role of organizational commitment and knowledge sharing - Arsawan, I Wayan Edi; Kariati, Ni Made; Shchokina, Yevheniia; Prayustika, Putu Adriani; Rustiarini, Ni Wayan; Koval, Viktor (Business: Theory and Practice, 2022)
Current research paper aimed to investigate determinants of employee’s innovative work behavior in export SMEs. The general problem in some export SMEs was a lack of knowledge implementation and employee innovation to provide problem-solving. It employed a quantitative method with administered questionnaires distributed to 177 employees of the exporting SMEs. The research data were evaluated using SmartPLS 3.2.7. The result shows that transformational leadership was notably associated to organizational commitment, knowledge sharing, as well as innovative work behavior. Also, organizational commitment and knowledge sharing are double mediators between transformational leadership and innovative work behavior. There are some limitations of this research paper, such as the bias effects of using a self-assessment report. The possible implication is that managers need to understand the relationship between variables, particularly mediating mechanisms, to provide insightful information for enhancing positive leadership performance and innovation capability – the originality point toward a mediating linkage of transformational leadership and innovative work behavior. The research paper enrich to a body of knowledge where innovative work behavior was influenced by leadership style and behavior and predictors of organizational behavior.